Uso de andrógenos e treino resistido em camundongos com osteoporose - Melo, Marcos Marini (2020)
Osteoporosis is the most common metabolic disorder in both humans and animals, which causes bone mass loss. This disorder affects more than 15% of humans aging more than 40 years of age. There had been a 55 % population increase of people aging over 60 years old within the period of 2001 and 2011. It is estimated that the Brazilian elderly population by the year 2050 will overcome the number of children and adults. The present study aims at evaluating the drug therapy (stanozolol 5mg/kg/week subcutaneously for 9 weeks, nandrolone decanoate 3mg/kg/week subcutaneously for also 9 weeks, and resistance exercise), in an experimental model of surgically induced osteoporosis in Swiss female mice aging 16 weeks. Osteoporosis was induced via bilateral ovariectomy, and soon after surgical procedure mice were kept at rest for 9 weeks. Assessment included live weight measurement and daily control of feed intake. Gastrocnemius and soleus muscle histomorphometric analysis were performed after euthanasia. Daily intake, body weight and muscle histomorphometric analysis proved to be sufficient to assess the effects of the tested drugs. Nevertheless, further studies are necessary to evaluate the combination of anabolic steroids and resistance exercises regarding osteoporosis alternative treatment.